DARI ALAT DIGITAL KE PRAKTIK AKUNTANSI: AI DALAM KEPUTUSAN KEUANGAN UMKM - Juwita Andriani; Wing Wahyu Winarno (E-Jurnal Akuntansi TSM, 2026)
This study aims to explore how Artificial Intelligence (AI) is interpreted and integrated into MSME accounting practices and its implications for financial decision-making. The research employs a qualitative approach with a case study design under an interpretive paradigm. Data were collected through in-depth interviews, limited observations, and documentation involving digital MSME owners who utilize accounting applications with AI features. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing, supported by triangulation to ensure credibility. The findings indicate that AI is initially perceived as an automation tool for transaction recording and financial reporting; however, over time, it contributes to the development of more adaptive, real-time, and data-driven accounting practices. The integration of AI enhances the quality of financial information particularly relevance, timeliness, and reliability which subsequently influences cost control, cash flow planning, and business performance evaluation decisions. Nevertheless, the effectiveness of AI utilization is shaped by digital literacy, human resource readiness, and organizational culture.